Ordinary differential equations an introduction to the fundamentals - Howell, Kenneth B. (Textbooks in mathematics, 2016)
Ordinary Differential Equations: An Introduction to the Fundamentals is a rigorous yet remarkably accessible textbook ideal for an introductory course in ordinary differential equations.